2017
DOI: 10.1590/s1980-6574201700010009
|View full text |Cite
|
Sign up to set email alerts
|

Can power and anaerobic capacity reduce according to disordered eating behaviors in cyclists?

Abstract: The present study aimed to compare the power, anaerobic capacity (AC) and performance in a road bicycle race among cyclists with and without risk of disordered eating behaviors (DEB). The sample was selected in a non-probabilistic way, totaling 69 male road cyclists aged between 19 and 30 years. The Wingate test was used to evaluate peak power (PP) and mean power. Time in minutes was adopted to determine performance in a 120-km road cycling race (competitive event). The Eating Attitudes Test (EAT-26) was compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…According to Skorski et al [ 83 ], in addition to and EM, anaerobic power and capacity are important factors that determine performance in road cycling. This is because in many road cycling races, first place can be decided in the final sprint, and cyclists with high anaerobic capacity and power can achieve better results [ 31 , 84 ]. Therefore, it may be important to determine the appropriate reduction time to optimize the power and anaerobic capacity of cyclists.…”
Section: Discussionmentioning
confidence: 99%
“…According to Skorski et al [ 83 ], in addition to and EM, anaerobic power and capacity are important factors that determine performance in road cycling. This is because in many road cycling races, first place can be decided in the final sprint, and cyclists with high anaerobic capacity and power can achieve better results [ 31 , 84 ]. Therefore, it may be important to determine the appropriate reduction time to optimize the power and anaerobic capacity of cyclists.…”
Section: Discussionmentioning
confidence: 99%
“…Of the identified studies, only one did not employ a self-reported cross-sectional measure of DE patterns. Qualitative research [ 41 ] and studies exploring the impact of DE on physiological outputs [ 57 ] are recommended to greater understand the impact of these behaviours on physical and mental health, well-being, and performance.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In addition, considering that athletes correlate performance improvement with body mass reduction 26 , it is possible that some athletes adopt DEB in order to enhance sports performance, which explains the high prevalence of DEB found in the present study (25%). It has been emphasized that muscle power can be reduced in athletes who adopt DEB 27 . Fortes et al 27 investigated male road cyclists and revealed that the adoption of DEB led to reduction in anaerobic performance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been emphasized that muscle power can be reduced in athletes who adopt DEB 27 . Fortes et al 27 investigated male road cyclists and revealed that the adoption of DEB led to reduction in anaerobic performance. According to these authors, the decrease in anaerobic power can be explained as a function of the reduction in the speed of the recruitment of motoneurons inherent to high-power muscle fibers, as well as reduction in the speed of action of the creatine kinase enzyme.…”
Section: Discussionmentioning
confidence: 99%